Effectiveness Of Negotiation As Instrument Of Peace In Resolving Apartheid South Africa Deep-Rooted Conflict - Adedeji, amos ojo (International Journal of Education, Vocational and Social Science, 2022)
Seeking peaceful means of resolving conflict instead of violent means make conflict to bedynamic. Negotiation, an Alternative Dispute Resolution (ADR) has been a viable tool ofconflict resolution in Africa. It played prominent roles in resolving South Africa apartheidconflict. The aim of the study was to interrogate the effectiveness of negotiation as theinstrument of peace in resolving apartheid South Africa deep-rooted conflict. The study revealedthat all strategies employed in the course of apartheid crisis failed until both parties returned tothe round table for negotiation. It was also established that the attitude of give and take(compromise) led to the resolution of the conflict. However, the strategy of negotiation was notproblem-free in the resolution of the South Africa apartheid conflict. The presence of the spoilerplayed destructive role of terminating the peace movement. The study concluded byrecommending embracement of peace and dialogue instead of violence in dealing with deep-rooted conflict